1975
DOI: 10.1002/ar.1091810202
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplet accumulation in cardiac muscle cells of the bat: Potential auto‐toxicity of the cardiac sympathetic innervation

Abstract: The previously described ability of reserpine and parachlorophenylalanine to induce the accumulation of lipid droplets in ventricular cardiac muscle cells of the bat was investigated. Lipid droplet accumulation was assessed qualitatively by light microscopy and quantitatively by morphometric analysis of electron micrographs. An hypothesis that the action of the drugs was an indirect one, mediated by the cardiac adrenergic innervation, was framed and tested. Lipid droplet accumulation occurred during a time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…1979: Hagopian and Nunez. 1972: Kawamura and James, 1971Kawamura et al" 1978: Nunez et al" 1975. However, in our studies on the West African straw-coloured (fruit-eating) bat Eidolon helvum, we have observed that the T-tubules in myocardial cells are subs tantially wider than in species such as the rat and that cyto plasmic organelles such as lipid droplets and mitochondria are much more numerous.…”
Section: Introductionmentioning
confidence: 59%
“…1979: Hagopian and Nunez. 1972: Kawamura and James, 1971Kawamura et al" 1978: Nunez et al" 1975. However, in our studies on the West African straw-coloured (fruit-eating) bat Eidolon helvum, we have observed that the T-tubules in myocardial cells are subs tantially wider than in species such as the rat and that cyto plasmic organelles such as lipid droplets and mitochondria are much more numerous.…”
Section: Introductionmentioning
confidence: 59%
“…Nunez et al [1975] suggested that these d roplets acc u m u la te i n t he myocard i u ni d uring times of intense sympathetic activity such as arousal from hibernation. Other cellular com ponents encountered in the nodal cells were Golgi apparatus, vacuoles, smooth and rough endoplasmic reticulum, glycogen deposits and subsarcolemmal vesicles.…”
Section: The Nodal Cellmentioning
confidence: 99%
“…When muscle damage or myopathy occurs, the satellite cells are activated and become myoblasts, then proliferate and differentiate into myotubes, and then form myofibers ( He et al, 2004 ). Most muscle disorders are accompanied by abnormal myoblast proliferation and myogenic differentiation ( Nunez et al, 1975 ). In addition, growing evidence has indicated that miRNA functions as a key regulator during myoblast proliferation and myogenic differentiation ( Altshuler-Keylin et al, 2016 ; Lu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%